Ecological status and trends of Lake Kastoria: Ten years of Biological Monitoring (Presentation) (2022)
Kemitzoglou D., E. Karadimou, S. Katsavouni, E. Mavromati, K. Moschandreou, V. Navrozidou, A. Patsia, M. Seferlis and V. Tsiaoussi. 2022. Ecological status and trends of Lake Kastoria: Ten years of Biological Monitoring. Presentation in Marine and Inland Waters Research Symposium 2022: former Panhellenic Symposium on Oceanography & Fisheries. Porto Heli, Argolida, Greece, 16-19 September 2022.